A liquid-liquid doping method for preparing a molybdenum oxide-based composite target

The method of liquid-liquid doping and in-situ reduction was used to prepare molybdenum oxide-based composite targets, which solved the problems of poor conductivity and difficulty in controlling oxygen content of molybdenum oxide targets. This method achieved high-density and high-conductivity molybdenum oxide-based composite targets, thereby improving the thin film quality and sputtering rate of perovskite solar cells.

CN122277248APending Publication Date: 2026-06-26JINDUICHENG MOLYBDENUM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610399417.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-03-30
Publication Date
2026-06-26

AI Technical Summary

Technical Problem

In the existing technology, the poor conductivity of molybdenum oxide targets and the difficulty in controlling oxygen content lead to slow sputtering rates and unstable film quality. Furthermore, the doping elements of inorganic metal oxides cannot be accurately controlled, which affects the performance of perovskite solar cells.

Method used

Molybdenum oxide-based composite targets were prepared using a liquid-liquid doping method. By adding substances such as nickel, potassium fluorotantalate, and niobium oxalate to an ammonium molybdate solution, adjusting the pH value, and precipitating the material, followed by drying and hot-pressing sintering, molybdenum oxide-based composite targets were formed. This method achieves in-situ reduction and doping, ensuring uniform composition and conductivity.

Benefits of technology

This study achieved controllable composition of molybdenum oxide-based composite targets, avoiding dopant segregation, improving the conductivity and density of the targets, enhancing the sputtering rate and quality of thin films, and meeting the performance requirements of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention discloses a liquid-liquid doping preparation method for molybdenum oxide-based composite targets. The disclosed method includes heating an ammonium molybdate solution with pH=6-6.5 to 60°C, adding an external dopant to the ammonium molybdate solution while stirring, then adding ammonia water to adjust the pH value to approximately 8.0, followed by rapid cooling to below -10°C while stirring; filtering and drying the crystals containing nickel hydroxide / tantalum hydroxide / niobium hydroxide that crystallize out during cooling, and then performing in-situ decomposition hot pressing sintering under a protected atmosphere to obtain a high-density molybdenum oxide-based composite target doped with Ni, Ta, and Nb oxides. The preparation method of this invention can prepare molybdenum oxide-based composite targets doped with Ni oxide, Ta oxide, and Nb oxides with uniform composition and good material conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of target preparation methods, and relates to a liquid-liquid doping preparation method for molybdenum oxide-based composite targets. Background Technology

[0002] A solar cell is a device that directly converts light energy into electrical energy through the photoelectric effect or photochemical reaction. Perovskite solar cells utilize perovskite-type organometal halide semiconductors as light-absorbing materials. Currently, promising materials for the hole transport layer in inverted perovskite solar cells include organic materials: poly(3,4) (ethylene dioxythiophene) Polystyrene sulfonic acid (PEDOT:PSS) and inorganic metal oxides: MoO3, NiO x PEDOT:PSS is expensive and hygroscopic, which can accelerate the decomposition of the perovskite light-absorbing layer and seriously endanger the stability of perovskite solar cells. In contrast, inorganic metal oxides are not only inexpensive but also have excellent chemical stability, and are considered as alternative materials to PEDOT:PSS.

[0003] Molybdenum oxide is a p-type semiconductor whose work function (approximately 5.3-5.7 eV) can be tuned by oxygen content, making it compatible with different semiconductor materials, such as perovskite valence band (5.4 eV) and crystalline silicon valence band (approximately 5.1 eV), thus making it suitable as an HTL material.

[0004] The deposition rate of molybdenum oxide thin films using reactive sputtering with molybdenum metal targets is slow, and oxygen poisoning can occur on the target surface, leading to abnormal discharges and severely affecting film quality and device yield. Furthermore, DC magnetron sputtering cannot be used with molybdenum oxide targets due to their poor conductivity. To improve conductivity, the oxygen content is typically adjusted during sputtering to create an oxygen-deficient state for molybdenum oxide, resulting in multi-valence molybdenum oxide particles and enhancing conductivity. However, this method cannot accurately and stably control the oxygen content, failing to guarantee the controllability of valence states in the oxygen-deficient state.

[0005] The patent (202080024251.7) mentions that adding doping elements, such as Ta and / or Nb, to a substoichiometric molybdenum oxide layer (and the corresponding sputtering target) can reduce the etching rate to an acceptable level without any substantial change in electro-optic properties, resulting in a material with poor electrical conductivity. Summary of the Invention

[0006] To address the shortcomings or deficiencies of existing technologies, this invention provides a liquid-liquid doping method for preparing molybdenum oxide-based composite targets.

[0007] Therefore, the liquid-liquid doping preparation method of the molybdenum oxide-based composite target provided by the present invention includes the following steps:

[0008] Step 1: Prepare a mixed aqueous solution of ammonium molybdate and an external dopant with a pH of 6-6.5 at 60±10℃. The external dopant is one or any two or more of nickel inorganic salt, potassium fluorotantalate and niobium oxalate. Step 2: Under conditions of 60±10℃, adjust the pH of the mixed aqueous solution prepared in Step 1 to 8±0.5, so that the foreign matter in the mixed aqueous solution will precipitate. Step 3: Cool the mixed aqueous solution after step 2 to below -10°C, and then collect the crystals in the cooling liquid; Step 4: After drying the crystals collected in Step 3, hot pressing and sintering are performed to obtain molybdenum oxide-based composite target material.

[0009] An optional approach is that step 1 includes: preparing an aqueous solution of ammonium molybdate with a pH of 6-6.5 at 60±10℃; then mixing the aqueous solution of ammonium molybdate with a pH of 6-6.5 with an aqueous solution of nickel inorganic salt at 60±10℃ to obtain an in-situ nickel-doped ammonium molybdate solution; and then mixing the in-situ nickel-doped ammonium molybdate solution with an aqueous solution of fluorotantalic acid and niobium oxalate to obtain a mixed solution.

[0010] An alternative approach is to have the following concentrations in the mixture from step 1: molybdate ion concentration of 1.3-3.5 mol / L, Ni ion concentration of 0.01-1.0 mol / L, tantalum ion concentration of less than or equal to 0.7 mol / L, and niobium ion concentration of less than or equal to 0.7 mol / L.

[0011] An alternative is to use ammonia to adjust the pH value in step 2.

[0012] An alternative is to set the cooling rate in step 3 to 5-10°C / min.

[0013] Alternatively, the nickel inorganic salt may be selected from one or more of nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate.

[0014] An alternative is to use a drying temperature of 65℃-100℃ in step 4 and dry for 6-8 hours to ensure that all the water for crystallization is lost.

[0015] An optional approach is that the hot pressing sintering in step 4 includes: firstly, gradually increasing the temperature to the hot pressing temperature of 700℃~850℃, setting a heat preservation step at 290-360℃ during the heating process, and holding the temperature for 60-120 minutes; then holding the temperature for 60 minutes to 240 minutes under an inert atmosphere, a hot pressing pressure of 10-35MPa, and a hot pressing temperature of 690℃~860℃.

[0016] Alternatively, the amount of nickel molybdate added can be adjusted according to the proportion of nickel content in the final molybdenum oxide-based composite target, and the amount of potassium fluorotantalate or niobium oxalate solution added can be adjusted according to the proportion of tantalum and niobium doped in the composite target. The mass percentage content of nickel oxide in the molybdenum oxide-based composite target ranges from 0 to 20%, the mass percentage content of tantalum oxide is 0 to 26.5%, and the mass percentage content of niobium oxide is 0 to 18%, and the mass percentage content of the three is not simultaneously 0.

[0017] An alternative is that the density of the molybdenum oxide-based composite target blank is greater than or equal to 98.5%.

[0018] This invention achieves uniform doping in the precursor of the raw material through liquid-liquid doping, and the doping amount can be adjusted according to the composition of the downstream target material. This not only ensures the controllability of the composition of the molybdenum oxide-based composite target material, but also avoids the problem of dopant element segregation caused by solid-solid doping.

[0019] Furthermore, this invention employs in-situ reduction of ammonium molybdate during hot-pressing sintering, thus achieving simultaneous in-situ reduction and hot pressing. The ammonia gas from the decomposition of ammonium molybdate can in-situ reduce molybdenum trioxide to oxygen-deficient molybdenum oxide. During the in-situ reduction sintering process, decomposition reactions of tantalum hydroxide, nickel hydroxide, and niobium hydroxide also occur. The H2O generated during this reaction gradually vaporizes and overflows from the mold, without affecting the target material preparation process. In this process, nickel hydroxide decomposes to obtain nickel oxide. Because it is surrounded by molybdenum oxide, a rich oxygen environment is formed, making it easier for nickel ions to fill positive ion vacancies, ensuring its high conductivity. Detailed Embodiments Unless otherwise specified, the scientific and technical terms used in this article are intended for understanding by those skilled in the art.

[0020] The present invention will now be described in detail with reference to specific embodiments. All raw materials used in the following embodiments are commercially available products.

[0021] Example 1: The liquid-liquid doping preparation method of the molybdenum oxide-based composite target in this embodiment is as follows: Step 1: Heat 1000 mL of ammonium molybdate aqueous solution with pH=6-6.5 and specific gravity=1.40 to 60℃. The molybdenum content in this solution is 325 g, and the molybdate ion content is 3.39 mol. Then, while stirring, add 16.4 mL of 1 mol / L nickel nitrate aqueous solution (Ni ion content is 0.0164 mol). Next, add 160 mL of potassium fluorotantalate and niobium oxalate aqueous solution, where the potassium fluorotantalate content is 19.4 g (tantalum ion content is 0.08 mol) and the niobium oxalate content is 16.25 g (niobium ion content is 0.08 mol). The resulting mixture has a molybdate ion concentration of 2.88 mol / L, a Ni ion concentration of 0.013 mol / L, a tantalum ion concentration of 0.68 mol / L, and a niobium ion concentration of 0.68 mol / L. Step 2: At 60℃, add 50mL of ammonia water to the mixed solution obtained in Step 1 to adjust the pH value to 8.0±0.5, so that the nickel inorganic salt, fluorotantalic acid and niobium oxalate in the mixed aqueous solution will precipitate. Step 3: The solution from Step 2 is rapidly cooled (cooling rate 5-10℃ / min) to below -10℃ while being stirred, and then the crystals in the cooling liquid are collected. Step 4: Dry the cooled crystals obtained in Step 3 (at 80℃ for about 7 hours) to remove the moisture. Analyze the dried material using the molybdenum constant method. The crystallinity of ammonium molybdate is 50%, yielding 300g of ammonium molybdate, 1.52g of nickel hydroxide, 21.82g of tantalum hydroxide, and 11.83g of niobium hydroxide. Further, load the dried powder into a graphite mold and perform hot pressing sintering. The hot pressing temperature is set to increase in stages, reaching 310±10℃ within 30 minutes, and then... The composite target was prepared by holding at 0°C for 120 min, then raising the temperature to 710±10°C for 60 min, pressurizing to 25 MPa, and holding at 710±10°C for 240 min under a nitrogen atmosphere. The composite target in this embodiment contains 89.2% molybdenum oxide, which is highly doped with Ni oxide (0.45%), Ta oxide (6.46%), and Nb oxide (3.89%).

[0022] The actual density of the composite target material in this embodiment, measured using the Archimedes displacement method, is 6.37 g / cm³. 3 The theoretical density is 6.45 g / cm³. 3 The density of the molybdenum oxide / nickel oxide composite target prepared in this embodiment was 98.7%.

[0023] Example 2: The difference between this embodiment and embodiment 1 is that: In step 1, 816 mL of a 1 mol / L nickel nitrate solution (containing 0.816 mol of Ni ions) was added to the ammonium molybdate solution under stirring. Then, 800 mL of a potassium fluorotantalate / ammonium niobate oxalate solution was added, wherein the amount of potassium fluorotantalate added was 97.7 g, with a tantalum content of 0.4 mol; and the amount of ammonium niobate oxalate added was 81.75 g, with a niobium content of 0.4 mol. The resulting mixture had a molybdate ion concentration of 1.3 mol / L, a Ni ion concentration of 0.31 mol / L, a tantalum ion concentration of 0.15 mol / L, and a niobium ion concentration of 0.15 mol / L. In step 2, 200 mL of ammonia water is added to the solution obtained in step 1 as a pH adjuster to adjust the pH value to about 8.0. In step 4, after drying, the crystallinity of ammonium molybdate in the cooled crystal is 50%, yielding 300g of ammonium molybdate, 75.7g of nickel hydroxide, 106.4g of tantalum hydroxide, and 59.16g of niobium hydroxide. The hot-pressing temperature during sintering is 840±10℃, with a step-up temperature of 340±10℃ and a holding time of 120min. The pressure during hot pressing is 35MPa, and the holding temperature is maintained for 240min. The resulting composite target material contains highly dense doped Ni oxide (13.65% by mass), Ta molybdenum oxide (19.8% by mass), and Nb oxide (11.9% by mass), with the remainder being molybdenum oxide.

[0024] Example 3: The difference between this embodiment and embodiment 1 is that: In step 1, 82 mL of a 1 mol / L nickel nitrate solution (Ni ion content of 0.082 mol) was added to the ammonium molybdate solution under stirring. Then, 320 mL of a potassium fluorotantalate / ammonium niobate oxalate solution was added, wherein the amount of potassium fluorotantalate added was 38.8 g, with an elemental content of 0.16 mol; the amount of ammonium niobate oxalate added was 32.5 g, with an elemental content of 0.16 mol. The resulting mixture had a molybdate ion concentration of 2.42 mol / L, a Ni ion concentration of 0.06 mol / L, a tantalum ion concentration of 0.11 mol / L, and a niobium ion concentration of 0.11 mol / L. In step 2, add 70 mL of ammonia water as a pH adjuster to adjust the pH value to approximately 8.0. In step 4, after drying, the crystallinity of ammonium molybdate in the cooled crystals was 50%, yielding 300g of ammonium molybdate, 7.6g of nickel hydroxide, 42.56g of tantalum hydroxide, and 23.67g of niobium hydroxide. The hot-pressing sintering conditions were: hot-pressing temperature of 800±10℃, with a stepped temperature increase, a holding step at 330±10℃, and a holding time of 100min; the hot-pressing pressure was 10MPa, and the holding time was 240min. The resulting composite target material was highly doped with Ni oxide (2.09% by mass), Ta molybdenum oxide (11.52% by mass), and Nb oxide (6.93% by mass).

[0025] Example 4: The difference between this embodiment and embodiment 1 is that: In step 1, 164 mL of a 1 mol / L nickel nitrate solution (containing 0.164 mol of Ni ions) was added to the ammonium molybdate solution under stirring. Then, 480 mL of a potassium fluorotantalate / ammonium niobate oxalate solution was added, wherein the amount of potassium fluorotantalate added was 58.2 g, containing 0.24 mol of tantalum; the amount of ammonium niobate oxalate added was 48.75 g, containing 0.24 mol of niobium. The resulting mixture had a molybdate ion concentration of 2.06 mol / L, a Ni ion concentration of 0.1 mol / L, a tantalum ion concentration of 0.15 mol / L, and a niobium ion concentration of 0.15 mol / L. In step 2, add 100 mL of ammonia water as a pH adjuster to adjust the pH value to approximately 8.0. In step 4, after drying, the crystallinity of ammonium molybdate in the cooled crystal is 50%, yielding 300g of ammonium molybdate, 15.2g of nickel hydroxide, 63.84g of tantalum hydroxide, and 35.5g of niobium hydroxide. The hot-pressing sintering conditions are as follows: hot-pressing temperature is 750±10℃, with a stepped temperature increase, a holding step at 350±10℃, and a holding time of 60min; the pressure during hot pressing is 25MPa, and the holding time is 60min. The resulting composite target contains highly dense doped Ni oxide (3.6% by mass), Ta molybdenum oxide (15.5% by mass), and Nb oxide (9.3% by mass).

[0026] Example 5: The difference between this embodiment and embodiment 1 is that: In step 1, 500 mL of 1 mol / L nickel nitrate solution (Ni ion content 0.5 mol) was added to the ammonium molybdate solution under stirring; 160 mL of potassium fluorotantalate / ammonium niobate oxalate solution was added, wherein the amount of potassium fluorotantalate added was 19.4 g, and the elemental content of tantalum was 0.08 mol; the amount of ammonium niobate oxalate added was 16.25 g, and the elemental content of niobium was 0.08 mol; the concentration of molybdate ions in the resulting mixture was 2.04 mol / L, the concentration of Ni ions was 0.3 mol / L, the concentration of tantalum ions was 0.05 mol / L, and the concentration of niobium ions was 0.05 mol / L. In step 2, add 120 mL of ammonia water as a pH adjuster to adjust the pH value to approximately 8.0. In step 4, the crystallinity of ammonium molybdate in the cooled crystal after drying is 50%, yielding 300g of ammonium molybdate, 46.35g of nickel hydroxide, 21.28g of tantalum hydroxide, and 11.83g of niobium hydroxide. The hot-pressing sintering conditions are as follows: hot-pressing temperature is 810±10℃, with a stepped temperature increase, a holding step at 350±10℃, and a holding time of 120min; the pressure during hot pressing is 20MPa, and the holding time is 120min. The resulting composite target contains highly dense doped Ni oxide (12.1% by mass), Ta molybdenum oxide (5.7% by mass), and Nb oxide (3.5% by mass).

[0027] Example 6: The difference between this embodiment and embodiment 1 is that: In step 1, 816 mL of a 1 mol / L nickel nitrate solution (Ni ion content of 0.816 mol) was added to the ammonium molybdate solution under stirring, along with 160 mL of a potassium fluorotantalate / ammonium niobate oxalate solution. The amount of potassium fluorotantalate added was 19.4 g, with a tantalum content of 0.08 mol; the amount of ammonium niobate oxalate added was 16.25 g, with a niobium content of 0.08 mol. The resulting mixture had a molybdate ion concentration of 1.7 mol / L, a Ni ion concentration of 0.4 mol / L, a tantalum ion concentration of 0.04 mol / L, and a niobium ion concentration of 0.04 mol / L. In step 2, add 70 mL of ammonia water as a pH adjuster to adjust the pH value to approximately 8.0. In step 4, the crystallinity of ammonium molybdate in the cooled crystal after drying is 50%, yielding 300g of ammonium molybdate, 75.7g of nickel hydroxide, 21.28g of tantalum hydroxide, and 11.83g of niobium hydroxide. The hot-pressing sintering conditions are as follows: hot-pressing temperature is 780±10℃, with a stepped temperature increase, a holding step at 350±10℃, and a holding time of 120min; the pressure during hot pressing is 25MPa, and the holding time at the hot-pressing temperature is 180min. The resulting composite target material contains highly dense doped Ni oxide (18.30% by mass), molybdenum oxide (5.3% by mass), and Nb oxide (3.19% by mass).

[0028] Example 7: The difference between this embodiment and embodiment 1 is that: In step 1, 816 mL of a 1 mol / L nickel nitrate solution (Ni ion content of 0.816 mol) was added to the ammonium molybdate solution under stirring; the resulting mixture had a molybdate ion concentration of 1.82 mol / L and a Ni ion concentration of 0.45 mol / L. In step 2, add 50 mL of ammonia water as a pH adjuster to adjust the pH value to approximately 8.0. In step 4, after drying, the crystallinity of ammonium molybdate in the cooled crystal is 50%, yielding 300g of ammonium molybdate and 75.7g of nickel hydroxide doped with it. The hot-pressing sintering conditions are as follows: hot-pressing temperature is 850±10℃, with a stepped temperature increase, a holding step at 330±10℃, and a holding time of 110min; the pressure during hot pressing is 35MPa, and the holding time at the hot-pressing temperature is 240min, resulting in a high-density molybdenum oxide-based composite target doped with Ni oxide (20% by mass).

[0029] Example 8: The difference between this embodiment and embodiment 1 is that: In step 1, 160 mL of potassium fluorotantalate / ammonium niobate oxalate solution was added to the ammonium molybdate solution under stirring. The amount of potassium fluorotantalate added was 19.4 g, and the elemental content of tantalum was 0.08 mol. The amount of ammonium niobate oxalate added was 16.25 g, and the elemental content of niobium was 0.08 mol. The concentration of molybdate ions in the resulting mixture was 2.92 mol / L, the concentration of tantalum ions was 0.07 mol / L, and the concentration of niobium ions was 0.07 mol / L. In step 2, add 150 mL of ammonia water as a pH adjuster to adjust the pH value to approximately 8.0. The crystallinity of ammonium molybdate in the dried and cooled crystals obtained in step 4 was 50%, with 300g of ammonium molybdate, 21.28g of tantalum hydroxide, and 11.83g of niobium hydroxide. The hot-pressing sintering conditions were as follows: hot-pressing temperature was 700±10℃, with a stepped temperature increase, a holding step at 300±10℃, and a holding time of 60min; the pressure during the hot-pressing process was 15MPa, and the holding time at the hot-pressing temperature was 120min, resulting in a molybdenum oxide-based composite target material with high density doped Ta molybdenum oxide (6.5% by mass) and Nb oxide (3.9% by mass).

[0030] Example 9: The difference between this embodiment and embodiment 1 is that: In step 1, 160 mL of ammonium niobate oxalate solution was added to the ammonium molybdate solution under stirring. The amount of ammonium niobate oxalate added was 16.25 g, and the elemental content of niobium was 0.08 mol. The concentration of molybdate ions in the resulting mixture was 1.82 mol / L, and the concentration of niobium ions was 0.07 mol / L. In step 2, add 50 mL of ammonia water as a pH adjuster to adjust the pH value to approximately 8.0. The crystallinity of ammonium molybdate in the dried and cooled crystals obtained in step 4 was 50%, with 300g of ammonium molybdate and 11.83g of niobium hydroxide. The hot-pressing sintering conditions were as follows: hot-pressing temperature was 700±10℃, with a stepped temperature increase, a holding step at 330±10℃, and a holding time of 60min; the pressure during the hot-pressing process was 15MPa, and the holding time at the hot-pressing temperature was 240min, resulting in a molybdenum oxide-based composite target with high density doped Nb oxide (4.17% by mass).

[0031] Example 10: The difference between this embodiment and embodiment 1 is that: In step 1, 160 ml of potassium fluorotantalate solution was added to the ammonium molybdate solution under stirring, wherein the amount of potassium fluorotantalate added was 19.4 g and the elemental content of tantalum was 0.08 mol; the concentration of molybdate ions in the resulting mixture was 1.82 mol / L and the concentration of tantalum ions was 0.07 mol / L. In step 2, add 70 mL of ammonia water as a pH adjuster to adjust the pH value to approximately 8.0. The crystallinity of ammonium molybdate in the dried and cooled crystals obtained in step 4 is 50%, with 300g of ammonium molybdate and 21.28g of tantalum hydroxide. The hot-pressing sintering conditions are as follows: hot-pressing temperature is 730±10℃, the hot-pressing temperature is set with a stepped increase, a heat preservation step is set at 325±10℃, and the heat preservation time is 90min; the pressure during the hot-pressing process is 25MPa, and the heat preservation time at the hot-pressing temperature is 240min, resulting in a molybdenum oxide-based composite target with high density doped Ta molybdenum oxide (mass percentage 6.75%).

[0032] Example 11: The difference between this embodiment and embodiment 1 is that: In step 1, 16.4 mL of a 1 mol / L nickel nitrate solution (Ni ion content of 0.0164 mol) was added with stirring; the resulting mixture had a molybdate ion concentration of 3.34 mol / L and a Ni ion concentration of 0.02 mol / L. In step 2, add 50 mL of ammonia water as a pH adjuster to adjust the pH value to approximately 8.0. In step 4, the crystallinity of ammonium molybdate obtained during drying and cooling crystallization was 50%, yielding 300g of ammonium molybdate and 1.52g of nickel hydroxide doped with it. The hot-pressing temperature was 700±10℃, with a stepped temperature increase and a holding step at 350±10℃ for 120min. The hot-pressing pressure was 35MPa, and the holding time was 240min, resulting in a high-density molybdenum oxide-based composite target doped with Ni oxide (0.50% by mass).

[0033] Example 12: The difference between this embodiment and embodiment 1 is that: In step 1, 82 mL of a 1 mol / L nickel nitrate solution was added with stirring, resulting in a Ni ion content of 0.082 mol; the resulting mixture contained a molybdate ion concentration of 3.13 mol / L and a Ni ion concentration of 0.08 mol / L. In step 2, add 55 mL of ammonia water as a pH adjuster to adjust the pH value to around 8.0. The crystallinity of ammonium molybdate obtained in step 4 during drying and cooling crystallization is 50%, yielding 300g of ammonium molybdate and 7.6g of nickel hydroxide doped with it. The hot pressing temperature is 800±10℃, with a stepped temperature increase and a holding step at 350±10℃ for 90min. The pressure during hot pressing is 25MPa, and the holding time is 120min, resulting in a high-density molybdenum oxide-based composite target doped with Ni oxide (2.47% by mass).

[0034] Example 13: The difference between this embodiment and embodiment 1 is that: In step 1, 164 mL of a 1 mol / L nickel nitrate solution was added with stirring, resulting in a Ni ion content of 0.164 mol. The resulting mixture contained a molybdate ion concentration of 2.91 mol / L and a Ni ion concentration of 0.14 mol / L. In step 2, add 65 mL of ammonia water as a pH adjuster to adjust the pH value to approximately 8.0. The crystallinity of ammonium molybdate obtained in step 4 during drying and cooling crystallization is 50%, yielding 300g of ammonium molybdate and 15.2g of nickel hydroxide doped with it. The hot pressing temperature is 750±10℃, with a stepped temperature increase and a holding step at 320±10℃ for 100min. The pressure during hot pressing is 25MPa, and the holding time is 180min, resulting in a high-density molybdenum oxide-based composite target doped with Ni oxide (4.8% by mass).

[0035] Comparative Example 1: This comparative example uses a hot pressing process to prepare high-purity nickel oxide targets. Specifically, nickel oxide powder is loaded into a graphite mold and hot-pressed under a protective atmosphere. The hot pressing process is as follows: hot pressing temperature 1100℃, holding temperature for 10h, and pressure during hot pressing is 15MPa.

[0036] Comparative Example 2: This comparative example uses a hot pressing process to prepare high-purity molybdenum trioxide targets. Specifically, molybdenum trioxide powder is loaded into a graphite mold and hot-pressed under a protective atmosphere. The hot pressing process is as follows: hot pressing temperature 650℃, holding temperature for 2 hours, and pressure during hot pressing is 25MPa.

[0037] Comparative Example 3: This comparative example uses a hot-pressing process to prepare high-purity molybdenum dioxide targets. Specifically, molybdenum dioxide powder is loaded into a graphite mold and hot-pressed under a protective atmosphere. The hot-pressing process is as follows: hot-pressing temperature 1050℃, holding temperature for 4 hours, and pressure 20MPa during the hot-pressing process.

[0038] The properties of the materials prepared in the above embodiments and multiple proportions were tested. The resistivity was tested using the four-probe method. The results are shown in Table 1. From the resistivity test results, the resistivity of Comparative Example 1 and Comparative Example 2 is relatively high. This will lead to severe target heating, a decrease in sputtering rate, and even affect the quality of the film. Therefore, downstream customers have put forward higher requirements for the resistivity of the target in order to improve the performance of the film.

[0039] The density of the target material was determined by measuring the actual density using the Archimedes displacement method, obtaining the theoretical density by calculating the theoretical density, and then using the ratio of the two to obtain the density.

[0040] This invention employs a liquid-liquid doping method, utilizing in-situ decomposition sintering to obtain composite targets that combine the advantages of both molybdenum oxide and nickel oxide. It introduces metal elements such as Ta / Nb, whose thin-film etching rate is controllable. This method is simple to operate, allows for adjustable component concentration, and produces targets with low resistivity and good conductivity (i.e., resistivity below 10⁻⁶). -3 Ω·cm).

[0041] Table 1

Claims

1. A method for preparing a molybdenum oxide-based composite target by liquid-liquid doping, characterized in that, The method includes the following steps: Step 1: Prepare a mixed aqueous solution of ammonium molybdate and an external dopant with a pH of 6-6.5 at 60±10℃. The external dopant is one or any two or more of nickel inorganic salt, potassium fluorotantalate and niobium oxalate. Step 2: Under conditions of 60±10℃, adjust the pH of the mixed aqueous solution prepared in Step 1 to 8±0.5, so that the foreign matter in the mixed aqueous solution will precipitate. Step 3: Cool the mixed aqueous solution after step 2 to below -10°C, and then collect the crystals in the cooling liquid; Step 4: After drying the crystals collected in Step 3, hot pressing and sintering are performed to obtain molybdenum oxide-based composite target material.

2. The method for preparing molybdenum oxide-based composite target material by liquid-liquid doping according to claim 1, characterized in that, Step 1 includes: preparing an aqueous solution of ammonium molybdate with a pH of 6-6.5 at 60±10℃; then mixing the aqueous solution of ammonium molybdate with a pH of 6-6.5 with an aqueous solution of nickel inorganic salt at 60±10℃ to obtain an in-situ nickel-doped ammonium molybdate solution; and then mixing the in-situ nickel-doped ammonium molybdate solution with an aqueous solution of fluorotantalic acid and niobium oxalate to obtain a mixed solution.

3. The method for preparing molybdenum oxide-based composite target material by liquid-liquid doping according to claim 1, characterized in that, In the mixture of step 1, the concentration of molybdate ions is 1.3-3.5 mol / L, the concentration of Ni ions is 0.01-1.0 mol / L, the concentration of tantalum ions is less than or equal to 0.7 mol / L, and the concentration of niobium ions is less than or equal to 0.7 mol / L.

4. The liquid-liquid doping preparation method of the molybdenum oxide-based composite target according to claim 1, characterized in that, In step 2, ammonia is used to adjust the pH value.

5. The liquid-liquid doping preparation method of the molybdenum oxide-based composite target according to claim 1, characterized in that, The cooling rate in step 3 is 5-10℃ / min.

6. The liquid-liquid doping preparation method of the molybdenum oxide-based composite target according to claim 2, characterized in that, The nickel inorganic salt is selected from one or more of nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate.

7. The method for preparing molybdenum oxide-based composite target material by liquid-liquid doping according to claim 1, characterized in that, The drying temperature in step 4 is 65℃-100℃, and the drying time is 6-8 hours to ensure that all the water for crystallization is lost.

8. The method for preparing molybdenum oxide-based composite target material by liquid-liquid doping according to claim 1, characterized in that, Step 4, hot pressing sintering, includes: first, stepwise heating to a hot pressing temperature of 700℃~850℃, setting a heat preservation step at 290-360℃ during the heating process, and holding at that temperature for 60-120 minutes; then holding at that temperature for 60 minutes~240 minutes under an inert atmosphere, a hot pressing pressure of 10-35MPa, and a hot pressing temperature of 690℃~860℃.

9. The method for preparing molybdenum oxide-based composite target material by liquid-liquid doping according to claim 1, characterized in that, The amount of nickel molybdate added can be controlled according to the proportion of nickel content in the final molybdenum oxide-based composite target. The amount of potassium fluorotantalate or niobium oxalate solution added can be controlled according to the proportion of tantalum and niobium doped in the composite target. The mass percentage content of nickel oxide in the molybdenum oxide-based composite target ranges from 0 to 20%, the mass percentage content of tantalum oxide is 0 to 26.5%, and the mass percentage content of niobium oxide is 0 to 18%, and the mass percentage content of the three is not 0 at the same time.

10. The method for preparing molybdenum oxide-based composite target material by liquid-liquid doping according to claim 1, characterized in that, The density of the molybdenum oxide-based composite target blank is greater than or equal to 98.5%.

Citation Information

Patent Citations

  • Sputtering target for preparing molybdenum oxide layer

    CN113614278B